The financial crisis and the global South: Impact and prospects - Yılmaz Akyüz; Vicente Paolo B. Yu (South Centre, 2017)
The world economy has not still recovered from the effects of the financial crisis that began almost a decade ago first in the US and then in Europe. Policy response to the crisis, the combination of fiscal restraint and ultra-easy monetary policy, has not only failed to bring about a robust recovery but has also aggravated systemic problems in the global economy, notably inequality and chronic demand gap, on the one hand, and financial fragility, on the other. It has generated strong destabilizing spillovers to the Global South. Major emerging economies that were expected a few years ago to become global locomotives have not only lost their momentum, but have also become highly vulnerable to trade and financial shocks. Policies proposed by the new administration in the US could entail a double blow to emerging and developing economies which have become highly dependent on foreign markets, capital and transnational corporations. The EU remains a global deadweight, generating deflationary impulses for the rest of the world economy. The jury is still out on whether the second largest economy, China, will be able to avoid financial turmoil and growth collapse. This state of affairs raises serious policy challenges to the Global South in responding to external shocks and redesigning the pace and pattern of their integration into the global economy so as to benefit from the opportunities that a broader economic space may offer while minimizing the potential risks it may entail.
Keywords: 300; Finanzkrise; Wirkungsanalyse; Wirtschaftliche Anpassung; Kapitalmobilität; Internationales Währungssystem; Finanzmarktregulierung; China; Entwicklungsländer; Welt